Aliovalent doping engineering enables multiple modulations of FeS2 anodes to achieve fast and durable sodium storage. Issue 39 (21st September 2022) - Yue, Luchao; Wang, Zhongxu; Wang, Dong; Song, Wei; Wu, Zhenguo; Zhao, Wenxi; Zhang, Longcheng; Luo, Yongsong; Sun, Shengjun; Zheng, Dongdong; Zhong, Benhe; Zhao, Jingxiang; et al.
Abstract : P doping regulates the electronic conductivity of FeS2 and induces charge redistribution around the doping sites to generate a local built-in electric field. As an anode in SIBs, P–FeS2 @C shows superior rate performance and cycling stability. Abstract : Metal sulfide anodes have trigged extensive academic progress in high-performance sodium-ion batteries (SIBs). However, their poor electronic conductivity and slack diffusion kinetics severely hinder their practical application. Herein, an efficient strategy to overcome the above-mentioned issues via heteroatom doping is proposed. As a demonstration, phosphorus-doped FeS2 nano-spindles encapsulated by a carbon layer (P–FeS2 @C) are produced and investigated as an anode material for SIBs. As expected, the as-designed P–FeS2 @C electrode presents a remarkably high specific capacity (624.4 mA h g −1 at 1.0 A g −1 after 100 cycles), admirable rate performance (401.2 mA h g −1 at 10.0 A g −1 ), and impressive cycling stability (285.4 mA h g −1 at 20.0 A g −1 over 4000 cycles). Furthermore, reaction kinetic analysis shows that the P–FeS2 @C anode presents a high capacitive contribution ratio and large diffusion coefficient of Na + during the sodium storage process compared with the undoped FeS2 @C. Simultaneously, density functional theory validates that P doping ameliorates the electronic structure of FeS2 and induces the formation of a local built-in electric field around the doping sites, reducing the diffusion energy carriers of Na + and accelerating the charge transport.